2010
DOI: 10.1080/09515089.2010.529048
|View full text |Cite
|
Sign up to set email alerts
|

Amusing ourselves to death? Superstimuli and the evolutionary social sciences

Abstract: Some evolutionary psychologists claim that humans are good at creating superstimuli, and that many pleasure technologies are detrimental to our reproductive fitness. Most of the evolutionary psychological literature makes use of some version of Lorenz and Tinbergen's largely embryonic conceptual framework to make sense of supernormal stimulation and bias exploitation in humans. However, the early ethological concept -superstimulus‖ was intimately connected to other erstwhile core ethological notions, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In evolutionary psychology, a supernormal stimulus or “superstimulus” is some evolutionarily novel concentration of engaging characteristics, which produces a stronger response than the natural one (1). As Pinker described it, strawberry cheesecake is a superstimulus as compared to a Neolithic human diet; it overloads the senses and drives caloric overconsumption, combining the “sweet taste of ripe fruit, the creamy mouth feel of fats and oils from nuts and meat, and the coolness of fresh water” (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In evolutionary psychology, a supernormal stimulus or “superstimulus” is some evolutionarily novel concentration of engaging characteristics, which produces a stronger response than the natural one (1). As Pinker described it, strawberry cheesecake is a superstimulus as compared to a Neolithic human diet; it overloads the senses and drives caloric overconsumption, combining the “sweet taste of ripe fruit, the creamy mouth feel of fats and oils from nuts and meat, and the coolness of fresh water” (2).…”
Section: Introductionmentioning
confidence: 99%
“…As Pinker described it, strawberry cheesecake is a superstimulus as compared to a Neolithic human diet; it overloads the senses and drives caloric overconsumption, combining the “sweet taste of ripe fruit, the creamy mouth feel of fats and oils from nuts and meat, and the coolness of fresh water” (2). The debate is ongoing as to what exactly differentiates a superstimulus from a regular one or whether it is truly maladaptive to create them or seek them out (1). Nevertheless, an important concept for neuroscience emerges from this discussion; certain systems governing the reaction to rewarding stimulus can be overloaded and their negative feedback component overridden.…”
Section: Introductionmentioning
confidence: 99%
“…For details, see DellaVigna & Linos [29] and Lin, Osman & Ashcroft [30]. For a defense of the idea that human beings are capable of resisting the pull of superstimuli, see De Block and Du Laing [31]. 15 Research by Thomson et al [32] has found, for example, that social media users do not display one of the main behavioral markers of addiction -that is, attentional bias towards social-media related stimuli.…”
Section: The Good Of the Attention Economymentioning
confidence: 99%
“…We evolved circuits that gave us trickles of enjoyment from the sweet taste of ripe fruit, the creamy mouth feel of fats and oils from nuts and meat, and the coolness of fresh water. Cheesecake packs a sensual wallop unlike anything in the natural world because it is a brew of megadoses of agreeable stimuli which we concocted for the express purpose of pressing our pleasure buttons" (Pinker, 1997, p. 524, cited in De Block andDu Laing 2010).…”
Section: Assessing Our Moral Capacities In a Hyper-constructed Cultural Niche: Fitness Functions And Supernormal Stimulimentioning
confidence: 99%
“…I have argued that the production of concerns about stigma, ethical taint, spiritual pollution and moral contamination that accompany moral judgments driven by disgust fit this description(Kelly 2011); also seePlakias (2013) for an opposing view of the value of disgust's contamination sensitivity when operating in the social domain.10 The concept has roots in classic ethology(Tinbergen 1951, Lorenz 1981), but has also appeared in more contemporary discussions concerning humans and human cognition; seeDe Block and Du Laing (2010) for examples and assessment of different applications of the idea in the social sciences.…”
mentioning
confidence: 99%